Topographic avenues for the Mediterranean outflow in the Gulf of Cadiz - Pelegrí, Josep Lluís; Gasser, Marc (2016)
XXXII Trobades Científiques de la Mediterrània, Planeta Oceà - Planet Ocean, celebradas del 5 al 7 de octubre de 2016 en Maó, Menorca.-- Homenatge als Drs. Marta Estrada, Jordi Font i Jordi Salat, pioners de l'oceanografia mediterrània moderna. A tribute to Drs. Marta Estrada, Jordi Font and Jordi Salat, pioneers of modern Mediterranean oceanography.-- 1 page The Mediterranean water (MW) exits the Strait of Gibraltar, past Espartel Sill, with salinity in excess of 38.5 and temperature ca. 13ºC, leading to water densities slightly greater than 1029.0 kg m-3. As it enters the Gulf of Cadiz, the MW encounters North Atlantic Central Water (NACW) with densities increasing with depth, from 1026.8 and 1027.2 kg m-3, between the base of the surface mixed layer to ca. 600 m. The MW-NACW density difference is initially so large that causes the Mediterranean outflow water (MOW) to behave as a density current: at early stages its thickness h=60-80 m and density anomaly delta dρ=2 kg m-3 leads to observed velocities of about 1.2-1.3 m s-1 - consistent with the theory (g h dρ/ρ)1/2 - and even greater over sloping channels. In the eastern Gulf of Cadiz, some 100-200 km from Espartell Sill, the MOW has deepened and mixed so the MW-NACW density difference has decreased to about one third of its initial value but the MOW thickness has roughly doubled, leading to density-driven currents still close to 1 m s-1, in agreement with observations. In this study, we examine the relevance of two main factors: how bottom topography steers the outflow along the bathymetric gradients and what is the role of the Coriolis force modifying these trajectories. For this purpose, we use an extensive hydrographic and velocity data set for the Gulf of Cadiz, combined with a high-resolution bathymetry, to explore the MOW pathways. The data is analyzed through three-dimensional perspective plots of salinity, temperature and velocity, and by tracking the maximum salinity anomalies. We also apply a classical method for determining hydrological avenues, ...